Pandemija covida-19 in njeni učinki na turistično ravnanje slovenskega prebivalstva - Cigale, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
The Covid-19 pandemic was a major shock to tourism around the world and in Slovenia. The number of tourist trips and overnight stays dropped sharply, and tourist flows were diverted. The paper presents the results of a survey, the aim of which was to deepen the knowledge about the impact of the Covid-19 pandemic on the tourist behavior of the Slovenian population. The results show that the pandemic influenced less frequent and shorter tourist trips and the choice of different tourist destinations. Travel decisions were influenced by both the role of epidemiological restrictions and perceptions of the safety of various forms of tourist travel, as well as the usual factors of tourist decision making.
Keywords: Covid-19; geography of tourism; pandemic; Pandemije; Slovenia; Slovenija; tourist behaviour; turistična geografija